Eosinophils Decrease Pulmonary Metastatic Mammary Tumor Growth - Cederberg, Rachel A.; Franks, Sarah Elizabeth; Wadsworth, Brennan J.; So, Alvina; Decotret, Lisa R.; Hall, Michael G.; Shi, Rocky; Hughes, Michael R.; McNagny, Kelly M.; Bennewith, Kevin L. (Frontiers in Oncology, 2022)
Metastatic breast cancer is challenging to effectively treat, highlighting the need for an improved understanding of host factors that influence metastatic tumor cell colonization and growth in distant tissues. The lungs are a common site of breast cancer metastasis and are host to a population of tissue-resident eosinophils. Eosinophils are granulocytic innate immune cells known for their prominent roles in allergy and Th2 immunity. Though their presence in solid tumors and metastases have been reported for decades, the influence of eosinophils on metastatic tumor growth in the lungs is unclear. We used transgenic mouse models characterized by elevated pulmonary eosinophils (IL5Tg mice) and eosinophil-deficiency (dblGATA mice), as well as antibody-mediated depletion of eosinophils, to study the role of eosinophils in EO771 mammary tumor growth in the lungs. We found that IL5Tg mice exhibit reduced pulmonary metastatic colonization and decreased metastatic tumor burden compared to wild-type (WT) mice or eosinophil-deficient mice. Eosinophils co-cultured with tumor cells ex vivo produced peroxidase activity and induced tumor cell death, indicating that eosinophils are capable of releasing eosinophil peroxidase (EPX) and killing EO771 tumor cells. We found that lung eosinophils expressed phenotypic markers of activation during EO771 tumor growth in the lungs, and that metastatic growth was accelerated in eosinophil-deficient mice and in WT mice after immunological depletion of eosinophils. Our results highlight an important role for eosinophils in restricting mammary tumor cell growth in the lungs and support further work to determine whether strategies to trigger local eosinophil degranulation may decrease pulmonary metastatic growth.